Kemampuan Orientasi Pasar Dan Kewirausahaan Untuk Meningkatkan Kinerja Pemasaran IKM Kerajinan Kain Sasirangan Melalui Kapabilitas Pemasaran Dinamis - Maryono; Taharuddin; Fitriyadi; Humaidi; Rizki Muslim Hidayat (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
This study aims to analyze the influence of market orientation and entrepreneurial orientation marketing performance, as well as the moderation effect of dynamic marketing capabilities. The research sample was taken as many as 102 Sasirangan fabric craftsmen in Banjarmasin City. The questionnaire was used to collect the data and further analyzed with SEM with Smart PLS. The results prove that marketing orientation has proven to have a significant effect on dynamic marketing capabilities, entrepreneurial orientation does not have a significant effect on marketing performance, while marketing capabilities have a significant effect on marketing performance. Research also found that dynamic marketing capabilities are proven to mediate marketing orientation and entrepreneurial orientation in their influence on marketing performance, it can be interpreted that dynamic marketing capabilities are mediating variables that strengthen marketing orientation and entrepreneurial orientation in influencing the marketing performance of sasirangan fabric industry craftsmen